PEMANFAATAN LAYANAN E-TICKETING COMMUTERLINE DALAM PENDISIPLINAN PERILAKU SOSIAL PADA PENGGUNA KRL DI STASIUN DEPOK LAMA - Zahra Raihanah (Mimbar Agama Budaya, 2020)
Abstract. Changes in the social behavior of KRL users, especially those of KRL users at Depok Lama Station, are one of the changes that have a significant impact on the progress of the Jabodetabek Commuter Line KRL transportation. This change was supported by the change in the KRL ticket purchasing system from paper tickets to E-Ticketing. The application of the E-Ticketing system to KRL transportation is one of the innovations launched by PT KAI in maximizing KRL transportation services. On the other hand, the application of the E-Ticketing system is also present as a solution in the midst of the problem of poor train service which causes train revenue to decline and the level of passenger confidence is also lower. For this reason, service improvements starting from the renovation of the station to the implementation of the E-Ticketing system are considered a way out to overcome the problems that occur. This article uses Anthony Giddens' structuration theory to understand how structures and agents collaborate to produce a new structure. Through the process of interviews, observation, and literature study, this article concludes that the implementation of the E-Ticketing system followed by several new policy implementations by PT KAI has been able to change the condition of the station area from dirty, slum, unsafe and comfortable and disorganized environment to better, cleaner, safer and more comfortable and systematic. In addition, the modernization of KRL services has also changed the culture of modern user behavior to be more orderly, disciplined and regular in using KRL transportation.Abstrak. Perubahan perilaku sosial pengguna KRL khususnya pada pengguna KRL di Stasiun Depok Lama menjadi salah satu perubahan yang berdampak signifikan bagi kemajuan transportasi KRL Commuter Line Jabodetabek. Perubahan ini ditunjang dengan berubahnya sistem pembelian tiket KRL dari paper ticket menjadi E-Ticketing. Penerapan sistem E-Ticketing pada transportasi KRL menjadi salah satu inovasi yang diluncurkan oleh PT KAI dalam memaksimalkan pelayanan transportasi KRL. Di sisi lain, penerapan sistem E-Ticketing juga hadir sebagai solusi ditengah masalah buruknya pelayanan kereta api sehingga menyebabkan pendapatan kereta api menurun dan tingkat kepercayaan penumpang juga semakin rendah. Untuk itu, perbaikan pelayanan dimulai dari renovasi ulang stasiun sampai penerapan sistem E-Ticketing dianggap sebuah jalan keluar untuk mengatasi masalah yang terjadi. Artikel ini menggunakan teori strukturasi dari Anthony Giddens untuk memahami bagaimana struktur dan agen saling berkolaborasi untuk menghasilkan sebuah struktur baru. Melalui proses wawancara, observasi, dan studi pustaka artikel ini menyimpulkan bahwa dengan diterapkannya sistem E-Ticketing diikuti dengan beberapa penerapan kebijakan baru oleh PT KAI ternyata mampu mengubah kondisi area stasiun dari yang kotor, kumuh, lingkungan yang tidak aman dan nyaman serta tidak terorganisir menjadi lebih baik, bersih, aman dan nyaman serta tersistematis. Disamping itu, modernisasi pelayanan KRL juga mengubah budaya perilaku modern pengguna nya menjadi  lebih tertib, disiplin, dan teratur dalam menggunakan transportasi KRL.Kata Kunci: